SOCIAL DEVELOPMENT REPORTS ON BRICS: VIOLATIONS TO FUNDAMENTAL HUMAN RIGHTS IN COMPARATIVE PERSPECTIVE - Strapazzon, Carlos Luiz; Zuana, Carolina Tissi Della (Unoesc International Legal Seminar, 2017)
This article was developed through meetings of study groups and documentary research. The results were based on<span title="Em grupos de estudo são discutidos os Relatórios da ONU sobre Direitos Humanos e Desenvolvimento e especificamente sobre os principais avanços e retrocessos normativos, institucionais e político-econômicos nos Estados que formam os BRICS (Brasil, Rússia, Índia, China e África do Sul) os"> the UN Reports on Human Rights and Development and specifically on the main normative, institutional and political-economic advances and setbacks in the BRICS States (Brazil, Russia, India, China and South Africa) are discussed. Which have been adopted by them in accordance with the ideals of social progress and substantive freedoms, of the UN development agenda. The conclusions based on documentary research on the development of freedoms related to the expansion of social rights in BRICS countries. <span title="Por outro lado, neste relatório constam análises das recomendações feitas aos cinco países, em documentos originais em inglês, sobre os direitos à saúde, pensão e assistência social e as deficiências ainda não superadas por eles no atendimento a realização desses direitos e ainda alguns avanços normativos">On the other hand, this report contains analyzes of the recommendations made to the five countries, in original documents in English, on the rights to health, pensions and social assistance, and the shortcomings they have not yet overcome in the fulfillment of these rights, as well as some normative advances, Institutional and political-economic in order to fulfill them.